2003
DOI: 10.1111/j.1741-4520.2003.tb01040.x
|View full text |Cite
|
Sign up to set email alerts
|

Infertility observed in female rats treated with N‐acetyl‐L‐cysteine: Histopathological examination of ovarian follicles and recovery of fertility

Abstract: We previously reported infertility in female rats that received N-acetyl-L-cysteine (NAC) intravenously at a dosage of 1000 mg/kg/day. Unfertilized oocytes and gestation day 1 and 2 embryos were assessed morphologically, and the results suggested that absence or thinning of the zona pellucida (ZP) is related to infertility. However, the morphological characteristics of oocytes before ovulation and recovery from the effects of NAC were not clarified. In the present study, the ovarian follicles were histopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, a study using a rat model demonstrated that intravenous NAC in high concentration (1000 mg.kg-1/day) promotes infertility probably due to an exacerbated thinning of the zona pellucida. 40 Thereby, further studies using animal models are needed to evaluate the effect of different concentrations of NAC to determine its efficacy and safety for embryos before its effects can be evaluated in infertile women with endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study using a rat model demonstrated that intravenous NAC in high concentration (1000 mg.kg-1/day) promotes infertility probably due to an exacerbated thinning of the zona pellucida. 40 Thereby, further studies using animal models are needed to evaluate the effect of different concentrations of NAC to determine its efficacy and safety for embryos before its effects can be evaluated in infertile women with endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of ZP2 (A) and ZP4 (B) transcripts was evaluated by RT-qPCR analysis MFCS = oocytes isolated from medium follicles of cycling sows, SFJG = oocytes from small follicles of juvenile gilts, SFCS = oocytes from small follicles of cycling sows Results are presented as mean ± SEM with the level of significance of P < 0.001 (*P < 0.01) a-c values with different superscripts are significantly different secondary sperm receptors, playing a significant role in gamete fusion during successful monospermic fertilization (Topfer-Petersen 1999). It has been previously shown in several species that oocytes lacking ZPs proteins are unable to fertilize (Harada et al 2003;Wassarman and Litscher 2012;Huang et al 2014). Ovarian follicle size significantly influences the ability of oocytes to mature and the gamete fertilizability.…”
Section: Discussionmentioning
confidence: 99%